The Influence of Work-Family Conflict on Employee Job Satisfaction Mediated by Job Burnout Among Employees of Bank Tabungan Negara in Padang City - Nasya Desta Fitri; Andriani, Chichi (Universitas Negeri Padang, 2025)
This study aims to examine: (1) the influence of Work-Family Conflict on Job Satisfaction, (2) the influence of Work-Family Conflict on Job Burnout, (3) the influence of Job Burnout on Job Satisfaction, and (4) the influence of Work-Family Conflict on Job Satisfaction mediated by Job Burnout. This research is a causal study with a population of 61 employees at Bank Tabungan Negara in Padang City, using a total sampling method. Data analysis was conducted using SmartPLS4 software. The findings of the analysis indicate that: (1) Work-Family Conflict has a negative and significant effect on Job Satisfaction among employees of Bank Tabungan Negara in Padang City, (2) Work-Family Conflict has a positive and significant effect on Job Burnout among employees of Bank Tabungan Negara in Padang City, (3) Job Burnout has a negative and significant effect on Job Satisfaction among employees of Bank Tabungan Negara in Padang City, and (4) Job Burnout mediates the effect of Work-Family Conflict on Job Satisfaction among employees of Bank Tabungan Negara in Padang City.